Pengaruh penerapan model pembelajaran problem based learning (PBL) terhadap hasil belajar IPAS Siswa Kelas IV SD N Randusari Yogyakarta - Ayulestari, Prima Desta; Murniningsih, Murniningsih; Bestiana Nizhomi; Megawati, Ida (Piramida Akademi, 2024)
This study aims to determine the effect of the application of the Problem Based Learning (PBL) learning model on the learning outcomes of IPAS fourth grade students of SD N Randusari Yogyakarta. This research is a Pre-Experimental Design research with One Group Pretest-Posttest Design design. The subjects of this study were fourth grade students of SD N Randusari Yogyakarta. Data collection techniques in this study using tests. Data analysis techniques using descriptive statistical analysis. Hypothesis testing uses non-parametric tests, namely the Mann-Whitney test. The results showed a very significant effect with the application of the Problem Based Learning (PBL) learning model on the learning outcomes of IPAS fourth grade students of SD N Randusari Yogyakarta. The effect of applying the Problem Based Learning (PBL) learning model can be seen from the increase in student pretest and posttest results. The average pretest score is 66.14 while the average posttest is 83.86. The results of the hypothesis test calculation using the Mann-whitney test found Asymp. Sig of 0.000. In accordance with the decision-making rules in the Mann-whitney test that the Asymp. Sig (2-tailed) <0.05 or 0.000 <0.05, this shows that the hypothesis is accepted. Learning outcomes increased through the average results of the pretest posttest obtained by students and the results of hypothesis testing, it was concluded that there was a very significant effect with the use of the Problem Based Learning (PBL) learning model on IPAS learning outcomes in fourth grade students of Randusari Yogyakarta State Elementary School.